Small Semi-Fossorial Herbivores Affect the Allocation of Above- and Below-Ground Plant Biomass in Alpine Meadows - Wang, Qian; Pang, Xiao Pan; Guo, Zheng Gang (Frontiers in Plant Science, 2022)
Small semi-fossorial herbivores can affect plant above-ground biomass (AGB) in grasslands and possibly alter the allocation of AGB and below-ground biomass (BGB). In this study, plateau pika (Ochotona curzoniae) was used to investigate such effects at three alpine meadow sites on the Eastern Tibetan Plateau, where pairs of disturbed vs. undisturbed plots were randomly selected and sampled. We also explored the relationships between soil properties and BGB/AGB across the plots in the presence and absence of plateau pikas, respectively. We found that BGB and BGB/AGB were 11.40% and 8.20% lower in the presence than in the absence of plateau pikas, respectively. We also found that the BGB/AGB was positively related to soil moisture and soil total nitrogen in the absence of plateau pikas. In contrast, BGB/AGB was positively related to soil total nitrogen, soil organic carbon, soil C/N, and soil total phosphorus in the presence of plateau pikas. These indicated Plateau pika disturbance increased AGB allocation. The relationships of AGB and BGB of alpine meadow plants to soil variables were also different between sites with and without plateau pika disturbance. In conclusion, small semi-fossorial herbivore disturbance is likely to alter grassland carbon stock and should be well controlled for sustainable conservation and management of alpine meadows on the Tibetan Plateau.